GAMBARAN PERSENTASE PENURUNAN ANGKA KUMAN GEL HAND SANITIZER DAN TISU BASAH ANTISEPTIK PADA TELAPAK TANGAN - Musfirah Musfirah (Jurnal Kesehatan dan Pengelolaan Lingkungan, 2021)
Diarrhea is the third order of disease in the Southeast Asian region that causes death in adolescents. Handwashing behavior is really important in preventing diarrhea in Indonesia. Antiseptic wet wipes and hand sanitizer gel are an acceptable alternative for washing hands with soap and air. The study aimed to determine the percentage reduction of hand sanitizer gel and wet-wipes antiseptic at the quantity of hand germs. This study used a quantitative descriptive study with a true experiment research design with a randomized pretest-posttest control group design. The research subjects were one respondent who will conduct 6 steps with any treatment 4 times of repetition. The results of univariate analysis showed that hand sanitizer â€œbrand Bâ€ and antiseptic wet tissue â€œbrand Bâ€ had a percentage reduction in the highest number of germs due to the existing treatment, respectively 80,49% and 73,55%. The percentage reduction of the germs number on the palms was found in hand sanitizer gel â€œbrand Bâ€ and antiseptic wet wipes â€œbrand Bâ€.